Acculturation of Islam and Culture in Shalawat Ngelik and Mauludan in Pathok Negoro Mosque Mlangi Yogyakarta - Dzulkifli Hadi Imawan; Muhammad Nurkhalid Al Ghazali (Potret Pemikiran, 2023)
This study describes the acculturation of Islam and local culture in Shalawat Ngelik and Kojan at the Maulidan Event at the Pathok Negoro Mlangi Mosque, Yogyakarta. Shalawat Ngelik is the recitation of Barjan's shalawat, which is read in a high voice at the time of the Mauludan event. Shalawat Ngelik and Kojan are typical Mlangi prayers that reflect the acculturation of culture and Islam, which have been rooted since the 18th century AD and have been maintained until now. For this reason, this study aims to explain the acculturation process of culture and Islam in the Ngelik and Kojan prayers at the Maulidan event at the Pathok Negoro Mlangi Mosque. This research method is a qualitative historical analysis approach. The results of this study explain that there is the acculturation of culture and Islam in the prayers of Ngelik and Kojan at the Maulidan event at the Pathok Negoro Mlangi Mosque, which can foster religious enthusiasm, care for traditions, and togetherness in the Mlangi community.